Apathy and striatal dopamine defects in non-demented patients with Parkinson's disease. (February 2016) - Chung, Su Jin; Lee, Jae Jung; Ham, Jee Hyun; Lee, Phil Hyu; Sohn, Young H.
Abstract: Introduction: Apathy is a common, disabling symptom in Parkinson's disease (PD). The mechanisms underlying apathy in PD are still unclear, although they may be related to dysfunction in the meso-cortico-limbic circuit, including the ventral striatum. Thus, we performed this study to investigate whether dopamine depletion in the ventral striatum contributes to apathy in PD. Methods: We conducted a survey of the degree of apathy (using the Korean version of the Apathy Evaluation Scale, AES-S) in 108 non-demented patients with PD who underwent dopamine transporter (DAT) positron emission tomography scans as an initial diagnostic work-up. Patients with AES-S scores of 37 or higher were defined as having apathetic PD. The Beck Depression Inventory (BDI) was administered to assess the severity of depression. Patients with BDI scores of 15 or higher were regarded as having depression. Results: Apathetic patients ( n = 34) tended to exhibit higher BDI scores than non-apathetic patients ( n = 74); however, other clinical variables were comparable between the two groups. DAT activity in the striatal sub-regions was also similar between the two groups. Selecting only non-depressed patients, including 20 apathetic and 47 non-apathetic patients, did not alter the results. Conclusions: This study demonstrated that the pattern of striatal dopamine depletion does not contribute to the degree of apathy in early PD. Apathy in PD may be associated with extra-striatal lesions that accompany PD rather than striatal dopaminergic deficits. Highlights: Apathy in non-demented Parkinson's disease (PD) is not associated with striatal dopamine transporter (DAT) binding. Pure apathy in PD (non-demented and non-depressed) is not associated with DAT binding to the striatal sub-regions. Apathy in PD may be associated with extra-striatal lesions that accompany in PD rather than striatal dopaminergic deficits.